Quantitative Assessment and Temporal Fluctuation of a Multiday Shrimp Trawl Bycatch off Digha Coast, West Bengal, India: Assessment of Bycatch from a Shrimp Trawler off Digha Coast - Jana, Susmita; Talagunda, Nagesh Srinivasan; Samanta, Rupam; Abraham, Thangapalam Jawahar; Behera, Samarendra; Bhakta, Dibakar (Fishery Technology, 2024)
Bycatch is one of the main issues affecting marine fisheries globally, and attempts have been made to understand the issue of bycatch at different scales. In India the bycatch issues in trawling have been reported widely. However, there are only scarce reports from northeast coast of India. The current study was carried out between July 2018 and March 2019 to assess the faunal composition, quantity of trawl bycatch and its seasonal fluctuation from a commercial multiday shrimp trawl (targeting shrimps and lobsters) operated along inshore areas off the Digha coast, West Bengal, India. Out of 145 finfish and shellfish species recorded, 130 species (104 species retained and 26 species discarded) were classified as bycatch. Sciaenids, crabs, shrimp, clupeids, Bombay duck, mollucsc, and elasmo branchs made up the bulk of the catch. The only species identified throughout the study period was Coilia dussumieri, but Harpadon nehereus was the most prevalent species that contributed to the weight as a single species. Gobies, angler fish, puffer fish, tripod fish, some crab species, stomatopods, octopus, gastropods, bivalves, and juveniles of high commercial value fishes were among the species that were discarded. Target catch, retained bycatch and discards constituted 9.4%, 54.8%, and 35.8% respectively of the overall catch. Use of bycatch reduction strategies, nets with better selectivity and seasonal ban on trawling is suggested for sustaining trawl fisheries along the coast.